(untitled) - Jessner, Ulrike (Edinburgh, 2006)
This book discusses cognitive and psycholinguistic aspects of third language acquisition and trilingualism, and explores the key role of linguistic awareness in multilingual proficiency and language learning. In view of the widespread acquisition of English by those who are already bilingual or are also acquiring a regional lingua franca this study will contribute to the current discussion of multilingualism with English in Europe and beyond, as well as the understanding of multilingual speech processing.
Nhận thức Anh ngữ
Keywords: Nhận thức ngôn ngữ,Language awareness